Destinasi Branding Candi Pari, Museum Mpu Tantular, dan Kampung Lawas Maspati dalam Memperkuat Identitas Budaya dan Daya Tarik Wisata - Virana Mega Putri; Alicia Indriani Putri; Hepy Amrelia; Mohammad Insan Romadhan (Tamasya : Jurnal Pariwisata Indonesia, 2025)
In exploring the important role of Candi Pari, the Mpu Tantular Museum, and Kampung Lawas Maspati as branding destinations, these sites significantly contribute to strengthening cultural identity and enhancing tourism appeal in East Java. Candi Pari, with its architectural beauty and historical value, serves not only as an attractive landmark but also as a profound symbol of cultural richness. The Mpu Tantular Museum functions as an information and educational center, housing collections of artifacts that reflect the historical journey and traditions of the local community, providing visitors with an educational experience. Kampung Lawas Maspati adds a unique dimension by offering visitors the opportunity to interact directly with the traditions and daily life of the local people. Through cultural preservation and the promotion of traditional activities, this village successfully attracts tourists seeking to experience the authenticity of Javanese culture. This article also discusses the branding strategies implemented to enhance the visibility and competitiveness of these three destinations in the tourism market. Through an integrated approach, these locations not only serve as tourist attractions but also as means to raise awareness of the importance of cultural preservation. Ultimately, this article emphasizes that developing tourist destinations based on local identity can have a positive economic impact on the community while preserving the region's rich cultural heritage